Evaluation of Shopee Food Usability Using Usability Testing Methods and System Usability Scale - Haminah, Siti; Pakaja, Fachrudin (oneamrd (One a Mllions Dreams Corporation), 2024)
This study aims to evaluate the Usability of the Shopee Food application using Usability Testing (UT) and the System Usability Scale (SUS) methods. The backdrop of this research is the significance of information technology in daily life, particularly in the use of mobile applications that facilitate various human activities. Shopee Food, as one of the popular food ordering applications in Indonesia, was chosen as the research object. Despite having a significant market share, the application still faces challenges in terms of navigation and ease of use. The methodology employed in this study includes a qualitative approach through UT conducted on 5 new users and a quantitative approach through SUS questionnaires filled out by 30 experienced Shopee Food application users. UT was conducted to identify issues faced by new users while using the application, whereas the SUS questionnaire was used to measure the satisfaction level of active users. The results indicate significant Usability issues with the Shopee Food application, particularly regarding the addition of vouchers and changing payment methods, which often confuse users. However, in terms of Learnability, Efficiency, Errors, and Satisfaction, the application demonstrates good performance. The Success Rate reached 98.57%, indicating users could complete tasks effectively. The average Time-Based Efficiency was 0.049 goals per second, the Error Rate at 22.8% is considered low, and the SUS score of 70 is above average, indicating a satisfactory level of user satisfaction. The conclusion of this study is that despite some Usability issues, the overall Usability level of the Shopee Food application is good. This research suggests improvements in the voucher addition feature and payment methods, as well as continuous Usability evaluations to ensure the application remains user-friendly and efficient